Colonial contexts and postcolonial theologies : storyweaving in the Asia-Pacific - Brett, Mark G. (Postcolonialism and religions., 2014)
Colonial Contexts and Postcolonial Theology focuses on what postcolonial theologies look like in colonial contexts, particularly in dialogue with the First Nations Peoples in Australia and the Asia-Pacific. The contributors have roots in the Asia-Pacific, but the struggles, theologies and concerns they address are shared across the seas. As a collection, this book is a work in "Storyweaving," which means, simply, the weaving of stories and memories that enliven journeys, traditions, histories and customs, with their pains and longings. A rich selection of theological themes and concerns are woven together in this book: the challenges of Postcolonialism; Theology as Struggle; rethinking Trinity in Samoa; cost of the Grand Canal Project in Korea; Postcolonial Samoan Hermeneutics; Empire in Postapocalyptic Mark; Indonesian Postcolonial Perspective; Natives in Pasifika; John Green as ngamadjidj; Masculinity and Missionaries; Law and Sovereignty; Terra Nullius Amnesiacs; Holy Communion with Indigenous elements; Homemaking; Acknowledging Traditional Owners; and Indigenous Perspective on Mission